The association of workplace violence with personal and work unit demographics, and its impact on nurse outcomes in the KwaZulu-Natal Province - Lyndelle Pillay; Siedine K. Coetzee; Nicholin Scheepers; Suria M. Ellis (Elsevier, 2023)
Aim: To examine the association of workplace violence (WPV) with personal and work unit demographics, as well as the relationship between WPV and nurse outcomes (job and career satisfaction, job and career turnover intention and mental and physical well-being) in the KwaZulu-Natal province. Background: Nurses are one of the population groups most susceptible to personal and physical WPV, and the association between WPV and nurse outcomes is well established. However, research in Africa is limited. Methods: A quantitative cross-sectional survey design was applied. Multiphase sampling was used to select (n = 405) nurses in KZN. Data was collected in April to August 2021 using self-report paper-based surveys in the public sector, and online self-report surveys in the private sector. Results: The nurses in this study report the most dissatisfaction with appreciation and rewards, about a fifth intend to leave their jobs and many present with sub-optimal physical and mental health. Personal and physical WPV had a medium to large correlation with all nurse outcomes, and nurses exposed to WPV had 2-3 times higher odds of experiencing poor nurse outcomes. Personal demographics, namely years worked as a nurse, years worked in current hospital, and having a clinical specialty were significantly associated with WPV. Work unit demographics, namely the healthcare sector worked in, the shift worked, rating of the practice environment, and the perpetrators were also significantly associated with WPV. Conclusions: Practice environments should be examined and initiatives to support nurses should be implemented, in the form of education, training and mentoring. Nurse managers should respond proactively and manage complaints of WPV, to create an environment of zero tolerance.